For a politics of atmospheric governance. (March 2015) - Feigenbaum, Anna; Kanngieser, Anja
A rise in social science scholarship on atmospheres has raised questions on how to articulate complex material and imperceptible events and encounters. Responding to Peter Adey's Air Affinities, this review proposes the need to traverse geopolitics and geopoetics to more fully engage these. Going further, it argues that such traversals are key to approaching specific situations and devices of what we call 'atmospheric policing'. Exploring recent examples of tear gas and sound warfare deployment in occupied Palestine, the review shows how discourses on atmospheres may be used to bring accountability into ecologies of violence.